2017
DOI: 10.1590/s0100-83582017350100039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Factors on Seed Germination and Emergence of Glyphosate Resistant and Susceptible Sourgrass

Abstract: -Sourgrass is one of the most problematic weeds of Brazil. It is an aggressive species in the allocation of resources from the environment and reported to be glyphosate resistant in several states of the country. This work has aimed to verify environmental effects on seed germination and seedling emergence of sourgrass. Laboratory and field trials were conducted to determine the effects of temperature, light, photoperiod, water availability and depth of burial in germination and emergence of seeds. The maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 24 publications
0
20
0
3
Order By: Relevance
“…The species of the genus Conyza, which have a high invasive potential due to the large seed production, the rapid and high germination capacity, cause great damage to agriculture, and due to their poor interspecific differentiation, it can be an exchange of resistant alleles between species [42]. However, D. insularis has been, among glyphosate resistant species, one of the main problems to be faced; therefore, greater efforts have been made to characterize the factors involved in its resistance, dispersal and management [12,[43][44][45][46][47][48]. Molecular studies showed that the first glyphosate resistant D. insularis populations found in the country (Guairá-Paraná) came from Paraguay…”
Section: Resistance To Epsps Inhibitorsmentioning
confidence: 99%
“…The species of the genus Conyza, which have a high invasive potential due to the large seed production, the rapid and high germination capacity, cause great damage to agriculture, and due to their poor interspecific differentiation, it can be an exchange of resistant alleles between species [42]. However, D. insularis has been, among glyphosate resistant species, one of the main problems to be faced; therefore, greater efforts have been made to characterize the factors involved in its resistance, dispersal and management [12,[43][44][45][46][47][48]. Molecular studies showed that the first glyphosate resistant D. insularis populations found in the country (Guairá-Paraná) came from Paraguay…”
Section: Resistance To Epsps Inhibitorsmentioning
confidence: 99%
“…O forte estímulo para quebra de dormência das sementes de Digitaria insularis poderia ser, ainda, intensificado pela simples deposição das sementes sobre o papel mata borrão, com grande disponibilidade de água, oxigênio e luz, sem os impedimentos representados pelo enterrio das sementes e presença de coberturas de solo (PETTER et al, 2015;MARTINS et al, 2017). Este fato poderia representar uma situação excepcionalmente favorável à germinação, uma vez que para Pereira et al (2017) a grande capacidade reprodutiva e de infestação seria inerente a espécies de grande agressividade e plasticidade ecológica como capim amargoso.…”
Section: Variáveisunclassified
“…Sourgrass (Digitaria insularis) is a perennial plant belonging to the Poaceae family that, under Brazilian conditions, can emerge and develop over the year (Martins et al, 2017). After its development and formation of rhizome, the difficulty of its control increases (Gemelli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%